1982
DOI: 10.1002/pol.1982.180200412
|View full text |Cite
|
Sign up to set email alerts
|

The structure of an aminosilane coupling agent in aqueous solutions and partially cured solids

Abstract: The molecular structures of partially cured polyaminopropylsilsesquioxane and aminopropyltriethoxysilane in water have been studied using Fourier‐transform infrared, laser Raman, and quasielastic laser light‐scattering spectroscopy. A multiply hydrogen‐bonded structure is proposed for the intramolecularly interacting amine and silanol groups on the basis of isotope exchange experiment and conformational energy calculations. Conformational restrictions are rather low for the proposed structure, which is thus su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 19 publications
0
28
1
Order By: Relevance
“…2b), the absorbance bands at 2923 and 2852 cm -1 are assigned to asymmetric and symmetric stretching vibration of >CH 2 , the strong and broad peak at 1029 cm -1 is the typical stretching absorbance band of Si-O-Si. The absorbance bands between 1650~1130 cm -1 are attributed to the stretching vibration of carbonyl group and bicarbonate salts due to the interaction between the amino group of γ-APS based components and environmental CO 2 and water Page 8 of 22 [34,35]. From the similarity between Fig.…”
Section: Analyses On Extractionsmentioning
confidence: 81%
“…2b), the absorbance bands at 2923 and 2852 cm -1 are assigned to asymmetric and symmetric stretching vibration of >CH 2 , the strong and broad peak at 1029 cm -1 is the typical stretching absorbance band of Si-O-Si. The absorbance bands between 1650~1130 cm -1 are attributed to the stretching vibration of carbonyl group and bicarbonate salts due to the interaction between the amino group of γ-APS based components and environmental CO 2 and water Page 8 of 22 [34,35]. From the similarity between Fig.…”
Section: Analyses On Extractionsmentioning
confidence: 81%
“…The high adsorption of VS on silica may be explained by the size effects. The VS molecule is smaller The estimated area occupied by a VS and a y-MPS molecule are 40 12/ 02 molecule [13] and 50 A /molecule, respectively [21].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, great attentions have been paid on the sizing structure or radial chemical composition to deepen the understanding of the correlation between the mechanical properties of composites and both the sizing and sizing technology. Post treatments and analyses [3,[26][27][28][29][30][31][32] on model reinforcements, especially 3-aminopropyltriethoxysilane (γ-APS) sized GF or silica, revealed that the surface of γ-APS sized model reinforcements consists of three layers, which are physically adsorbed, chemisorbed, and chemically covalent bonded polysiloxanes from air/sizing interface to sizing/GF interface [29][30][31]. It was found that the physically adsorbed polysiloxanes based on γ-APS have a detrimental effect on the GF-matrix adhesion strength [33].…”
Section: Introductionmentioning
confidence: 99%